Pengaruh Gaya Mengajar Guru IPS Terhadap Motivasi Belajar Siswa SMAN 1 Woja Tahun Pembelajaran 2023/2024 - Sulaiman, Sulaiman; Sumiyati, Sumiyati; Arifin, Arifin; Julita, Putri; Putri, Sakila (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Teaching variation is a teacher's activity in the learning interaction process which is aimed at overcoming student boredom by creating an environment that encourages and allows the learning process to take place through changes in teaching styles, changing media used, and changes in interaction patterns between students and teachers. This research aims to determine the influence of teacher teaching style on student learning motivation. The problem to be answered is whether there is an influence of the teacher's teaching style on the social studies learning motivation of class X students at SMAN 1 Woja for the 2023/2024 academic year. The type of research used is correlation with a quantitative approach. The population in this study was all students of X SMAN 1 Woja, totaling 155 students and the class sampled was class X SMAN 1 Woja, totaling 18 students. Sampling is sampling carried out with a specific purpose (Purposive Sampling). From the results of the analysis, linearity calculations show that Fcount is 3.06, < Ftable = 3.29, for the significance test, the result is Fcount 11.57 > Ftable 4.49, and from the hypothesis test of the relationship, rcount is 0.650 > Rtable 0.468, the coefficient of determination amounting to r2xy = 0.4225, which means that 42.25% of the influence of the teacher's teaching style can increase student learning motivation, through the regression equation Y = 4.06 + 0.80 X, the remaining 57.25% is determined by other factors. So it can be stated that the null hypothesis (Ho) is rejected and the analytical hypothesis (Ha) is accepted.